Heterochromatin protein 1a functions for piRNA biogenesis predominantly from pericentric and telomeric regions in Drosophila - Teo, Ryan Yee Wei (2018)
In metazoan germline, Piwi-interacting RNAs (piRNAs) provide defence against transposons. Piwi–piRNA complex mediates transcriptional silencing of transposons in nucleus. Heterochromatin protein 1a (HP1a) has been proposed to function downstream of Piwi-piRNA complex in Drosophila. Here we show that HP1a germline knockdown (HP1a-GLKD) leads to a reduction in the total and Piwi-bound piRNAs mapping to clusters and transposons insertions, predominantly in the regions close to telomeres and centromeres, resulting in derepression of a limited number of transposons from these regions. In addition, HP1a-GLKD increases the splicing of transcripts arising from clusters in above regions, suggesting HP1a also functions upstream to piRNA processing. Evolutionarily old transposons enriched in the pericentric regions exhibit significant loss in piRNAs targeting these transposons upon HP1a-GLKD. Our study suggests that HP1a functions to repress transposons in a chromosomal compartmentalised manner.